Novel Polymorphisms and Genetic Characteristics of the Prion Protein Gene in Pheasants - Kim, Kyung Han; Kim, Yong-Chan; Jeong, Byung-Hoon (Frontiers in Veterinary Science, 2022)
Transmissible spongiform encephalopathies (TSEs) also known as prion diseases, are fatal neurodegenerative diseases. Prion diseases are caused by abnormal prion protein (PrPSc) derived from normal prion protein (PrPC), which is encoded by the prion protein gene (PRNP). Prion diseases have been reported in several mammals. Notably, chickens, one species of bird, have not been reported to develop prion diseases and show resistance to bovine spongiform encephalopathy (BSE) infection. However, genetic polymorphisms of the PRNP gene and protein structure of the prion protein (PrP) related to vulnerability to prion diseases have not been investigated in pheasants, another species of bird. We performed amplicon sequencing of the pheasant PRNP gene to identify genetic polymorphisms in 148 pheasants. We analyzed the genotype, allele and haplotype frequencies of the pheasant PRNP polymorphisms. In addition, we evaluated the effect of genetic polymorphisms of the pheasant PRNP gene on pheasant PrP by the AMYCO, PROVEAN, PolyPhen-2 and PANTHER programs. Furthermore, we compared the amino acid sequences of tandem repeat domains and secondary and tertiary structures of PrPs among several animals. Finally, we investigated the impact of nonsynonymous SNPs on hydrogen bonds and tertiary structures of pheasant PrP by Swiss PDB viewer software. We identified 34 novel genetic polymorphisms of the pheasant PRNP gene including 8 nonsynonymous SNPs and 6 insertion/deletion polymorphisms in 148 pheasants. Among the nonsynonymous SNPs, the L23F, G33C and R177Q SNPs showed a deleterious effect on pheasant PrP. In addition, the R177Q SNP was predicted to show an increase in amyloid propensity and a reduction in hydrogen bonds of pheasant PrP. Among the insertion/deletion polymorphisms, c.163_180delAACCCGGGGTATCCCCAC showed a detrimental effect on pheasant PrP. Furthermore, secondary and tertiary structures of pheasant PrP were predicted to have structures similar to those of chicken PrP. To the best of our knowledge, this is the first study on genetic polymorphisms of the pheasant PRNP gene.